Flattening the Curve of Moral Imagination - Beran, Ondřej (My University, 2022)
In this paper, I discuss some moral dilemmas related to the COVID-19 crisis and their framing (mainly) in the public debate. The key assumption to engage with is this: that we need primarily to take into account the long-term economic consequences of the pro-posed safety measures of social distancing. I argue that the long-term economic concerns, though legitimate, cannot suspend the irreducibly moral nature of the demand placed on the decision-makers by those who are vulnerable, at risk, or in need of medical treatment. This is discussed in relation to two points: 1) The political endeavour and rhetoric of "flattening the curve" is not necessarily short-sighted, but expresses the acknowledgment of a legitimate expectation placed on elected representatives. 2) Not being able to prevent harm (to those who are in real need, or otherwise vulnerable) may lead to a genuine moral distress, even if it is not clear whether it was in one's, or any-body's, powers to prevent the situation, or even if the best possible outcome has been otherwise reached. The second point may be un-derstood as a part of the broader context of the established criticisms of utilitarianism.
Zploštit křivku morální imaginace
Keywords: COVID-19 crisis; economic concerns; moral dilemmas; moral luck; remorse